Comparison of Fasting Blood Glucose and HbA1c Levels in Patients with Type 2 Diabetes Mellitus Based on Physical Activity - Tuames, Yohana Berlina Saraswati; Setianingrum, Elisabeth Levina; Asa, Halena Meldy; Adang, Gottfrieda Patiencia Taeng-Ob (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Type 2 diabetes mellitus is a prevalent non-communicable disease associated with serious complications. Physical activity is a modifiable risk factor that plays an important role in glycemic control. This study aimed to analyze differences in fasting blood glucose and glycated hemoglobin (HbA1c) levels based on physical activity levels among patients with type 2 diabetes mellitus at primary health care centers in Kupang City. An analytic observational study with a cross-sectional design was conducted involving 71 respondents selected through consecutive sampling. Physical activity levels were assessed using the Global Physical Activity Questionnaire (GPAQ). fasting blood glucose was measured from capillary blood samples, while HbA1c was obtained from venous blood samples. Data were analyzed using univariate and bivariate methods, and mean differences across PA categories were tested using one-way ANOVA. The results showed no statistically significant differences in fasting blood glucose (p = 0.610) or HbA1c (p = 0.283) based on physical activity levels. In conclusion, physical activity level was not significantly associated with fasting blood glucose or HbA1c among patients with type 2 diabetes mellitus at primary health care centers in Kupang City. These findings suggest that optimal glycemic control requires a holistic approach, including physical activity, treatment adherence, and dietary management.Keywords: physical activity; fasting blood glucose; glycated hemoglobin; type 2 diabetes mellitus; primary health care centers